2003
DOI: 10.1073/pnas.0731952100
|View full text |Cite
|
Sign up to set email alerts
|

A new Drosophila spliceosomal intron position is common in plants

Abstract: The 25-year-old debate about the origin of introns between proponents of ''introns early'' and ''introns late'' has yielded significant advances, yet important questions remain to be ascertained. One question concerns the density of introns in the last common ancestor of the three multicellular kingdoms. Approaches to this issue thus far have relied on counts of the numbers of identical intron positions across present-day taxa on the assumption that the introns at those sites are orthologous. However, dismissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Homoplastic gains represent 5-20% of shared intron positions (8,9,27,28). Although the potential for homoplastic gain decreases with the divergence in the sample, closely related sequences are prone to it by virtue of their high similarity (provided gains do not occur at random) (29). Studies of closely related species that use distantly related outgroups (e.g., 15,17,21,22) have enhanced likelihood of parallel gain.…”
Section: Resultsmentioning
confidence: 99%
“…Homoplastic gains represent 5-20% of shared intron positions (8,9,27,28). Although the potential for homoplastic gain decreases with the divergence in the sample, closely related sequences are prone to it by virtue of their high similarity (provided gains do not occur at random) (29). Studies of closely related species that use distantly related outgroups (e.g., 15,17,21,22) have enhanced likelihood of parallel gain.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that intron loss may occur through qualitatively different mechanisms in nematodes. Kent and Zahler (41) offer the interesting observation that the 5Ј and 3Ј boundaries of unique introns between C. elegans and Caenorhabditis briggsae show greater similarity to each other than do the boundaries of control introns, and suggested that introns may be lost by nonhomologous recombination between intron boundaries [although their result could also be explained by preferential intron insertion into sites with a consensus sequence of AG͉GT (17,(27)(28)(29)(30)(31)(32)(33)(34)]. Comparative analyses of multiple nematode genomes should help to better understand these deviations.…”
Section: Discussionmentioning
confidence: 99%
“…First, the biases could be echoes of gene formation through combination of exons or groups of exons (3-7, 9, 23-26) mediated by ancient phase zero introns (23). Second, intron insertion might be phase-biased (5,8,16,(27)(28)(29)(30)(31)(32)(33)(34), perhaps due to preferential insertion into sites which themselves happen to be phase-biased (although, see ref. 7).…”
mentioning
confidence: 99%
“…Intron-exon structure relationship and intron evolution in genes have been a debating focus of evolutionary biology (Tarrio, Rodriguez-Trelles & Ayala, 2003). Recently, intron loss and its evolutionary significance have been noted in Drosophila.…”
Section: Discussionmentioning
confidence: 99%